2013
DOI: 10.1371/journal.pone.0069963
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Phosphoribosyl Transferase (Nampt) Is a Target of MicroRNA-26b in Colorectal Cancer Cells

Abstract: A number of cancers show increased expression of Nicotinamide phosphoribosyl transferase (Nampt). However, the mechanism through which Nampt is upregulated is unclear. In our study, we found that the Nampt-specific chemical inhibitor FK866 significantly inhibited cell survival and reduced nicotinamide adenine dinucleotide (NAD) levels in LoVo and SW480 cell lines. Bioinformatics analyses suggested that miR-26b targets Nampt mRNA. We identified Nampt as a new target of miR-26b and demonstrated that miR-26b inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 44 publications
14
55
0
Order By: Relevance
“…S4), it is possible that reduced miR-26 levels in tumors is a secondary consequence of impaired differentiation of tumor epithelial cells. Nevertheless, taken together with our functional data from Apc min/+ mice and previous studies that have demonstrated anti-tumorigenic effects of miR-26 expression in human CRC cell lines (Ma et al 2011;Zhang et al 2013), these data strongly suggest a tumor suppressor role for miR-26 in human colon cancer.…”
Section: Reduced Expression Of Mir-26 In Human Crcsupporting
confidence: 79%
See 1 more Smart Citation
“…S4), it is possible that reduced miR-26 levels in tumors is a secondary consequence of impaired differentiation of tumor epithelial cells. Nevertheless, taken together with our functional data from Apc min/+ mice and previous studies that have demonstrated anti-tumorigenic effects of miR-26 expression in human CRC cell lines (Ma et al 2011;Zhang et al 2013), these data strongly suggest a tumor suppressor role for miR-26 in human colon cancer.…”
Section: Reduced Expression Of Mir-26 In Human Crcsupporting
confidence: 79%
“…While previous studies have documented anti-tumorigenic effects of miR-26 expression in CRC cell lines (Ma et al 2011;Zhang et al 2013), the significance of these results has remained unclear, since miRNA profiling studies have inconsistently detected miR-26 down-regulation in human colorectal tumors (Schepeler et al 2008;Schetter et al 2008;Motoyama et al 2009;Ma et al 2011;Gaedcke et al 2012). The cellular heterogeneity of normal and neoplastic intestinal tissue can confound the detection of abnormally expressed genes within tumor epithelial cells, the relevant transformed cell type.…”
mentioning
confidence: 99%
“…Based on a large analysis of genes associated with GDM, it was proposed that these genes might be further classified as (a) insulin secretion genes; (b) insulin and insulin signaling genes; (c) lipid and glucose metabolism genes; (d) maturity-onset diabetes of the young (MODY) genes; and (e) other genes (Robitaille and Grant, 2008). Most genetic variants associated with GDM and were significantly associated with a higher risk of GDM (Zhang et al, 2013a(Zhang et al, , 2013b.…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“…The miR-26b expression is frequently abnormal in tumors, indicating that miR-26b plays a significant role in cancer development (20). The miR-26b level is significantly up-regulated in bladder cancer (21), whereas it is down-regulated in liver cancer (22), colorectal cancer (23), and human breast cancer (24,25). miR-26b could serve as a tumor suppressor in colorectal cancer and in glioma (23,26).…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 99%
“…The miR-26b level is significantly up-regulated in bladder cancer (21), whereas it is down-regulated in liver cancer (22), colorectal cancer (23), and human breast cancer (24,25). miR-26b could serve as a tumor suppressor in colorectal cancer and in glioma (23,26). Chronic HBV infection is one of the main causes of hepatocellular carcinoma (HCC), and many miRNAs have essential roles in liver cancer progression by directly targeting a large number of crucial genes in HCC cells (27).…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 99%